Islamic Education Financing Management Model - Samsudin, Agus; Sanusi, Iwan; Firdaus, Jannatun (STAI AL-FALAH CICALENGKA, 2021)
Financing is one of the important elements in educational institutions. One indicator of a good school is the high cost, but the complexity of financing in educational institutions is one of the factors inhibiting the quality and progress of these educational institutions, therefore there needs to be efforts and models in managing financing in educational units towards achieving the vision and mission of educational institutions, especially institutions. Islamic education. The method used in the implementation of this study was a descriptive analysis method with a qualitative approach. With data collection techniques through interviews, observation, and documentation. The results of the study illustrate, in planning for financing management through annual work meetings that are integrated with the Madrasah Activity Plan and Budget (RKAM) in accordance with technical guidelines (technical instructions) for the use of BOS funds. In the process of developing the RKAM, the madrasah holds a meeting of the foundation leadership, headmaster, educators, education staff and programmed madrasah committees. In its implementation, it refers to the madrasah program according to its time schedule. In the evaluation of financing, madrasah makes an accountability report book (LPJ), programs that have not been realized and are considered important will be resubmitted to the next program, programs that have been implemented if deemed important will continue to be budgeted for in the next program based on good and periodic control. Keywords: Management Model, Financing, Islamic Education Abstrak Pembiayaan salah satu unsur penting dalam lembaga pendidikan. Salah satu indikator sekolah bagus biayanya tinggi, namun kompleksnya pembiayaan di lembaga pendidikan menjadikan salah satu faktor penghambat kualitas dan kemajuan lembaga pendidikan tersebut, oleh karena itu perlu ada upaya dan model dalam mengelola pembiayaan di satuan pendidikan menuju tercapai visi dan misi lembaga pendidikan, terkhusus lembaga pendidikan Islam. Metode yang digunakan dalam pelaksanaan penelitian ini adalah metode deskriptif analisis dengan jenis pendekatan kualitatif. Dengan teknik pengumpulan data melalui wawancara, observasi, dan dokumentasi. Hasil penelitian menggambarkan, dalam melakukan perencanaan terhadap manajemen pembiayaan melalui rapat kerja tahunan yang terintegrasi dengan Rancangan Kegiatan dan Anggaran Madrasah (RKAM) sesuai dengan juknis (petunjuk teknis) penggunaan dana BOS. Dalam proses pengembangan RKAM, madrasah mengadakan rapat pimpinan yayasan, kepala madrasah, pendidik, tenaga kependidikan dan komite madrasah yang terprogram. Dalam pelaksanaanya, mengacu pada program madrasah sesuai time schedule-nya. Dalam evaluasi pembiayaan, madrasah membuat buku laporan pertangungjawaban (LPJ), program yang belum terealisasi dan dianggap penting nantinya akan diajukan ulang pada program berikutnya, program yang sudah terlaksanakan jika dianggap penting maka akan terus dianggarkan pada program berikutnya berdasarkan kontrol yang baik dan berkala. Kata Kunci: Model Manajeman, Pembiayaan, Pendidikan Islam